2014
DOI: 10.2147/jir.s61471
|View full text |Cite
|
Sign up to set email alerts
|

Effect of plant extracts on H2O2-induced inflammatory gene expression in macrophages

Abstract: BackgroundArctium lappa (AL), Camellia sinensis (CS), Echinacea angustifolia, Eleutherococcus senticosus, Panax ginseng (PG), and Vaccinium myrtillus (VM) are plants traditionally used in many herbal formulations for the treatment of various conditions. Although they are well known and already studied for their anti-inflammatory properties, their effects on H2O2-stimulated macrophages are a novel area of study.Materials and methodsCell viability was tested after treatment with increasing doses of H2O2 and/or p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 73 publications
(75 reference statements)
0
11
0
Order By: Relevance
“…Blueberry blocked the activation of nuclear factor kβ and expression of nitric oxide synthase-2, cyclooxygenase-2, interleukin-1β (IL-1β), and tumor necrosis factor-α (TNF-α) in H 2 O 2 -stimulated macrophages. [ 6 35 ] Cranberry (CRAN) increased SOD, CAT and GPX activity in liver and reduce TNF-α, after exposition to gamma radiation. [ 36 ] Moreover, polyphenols from Cranberry improved mitochondrial dysfunctions in intestinal Caco-2/15 cells stimulated with com lipopolysaccharide (LPS), which alleviate intestinal oxidative stress and inflammation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Blueberry blocked the activation of nuclear factor kβ and expression of nitric oxide synthase-2, cyclooxygenase-2, interleukin-1β (IL-1β), and tumor necrosis factor-α (TNF-α) in H 2 O 2 -stimulated macrophages. [ 6 35 ] Cranberry (CRAN) increased SOD, CAT and GPX activity in liver and reduce TNF-α, after exposition to gamma radiation. [ 36 ] Moreover, polyphenols from Cranberry improved mitochondrial dysfunctions in intestinal Caco-2/15 cells stimulated with com lipopolysaccharide (LPS), which alleviate intestinal oxidative stress and inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…[ 5 ] BLUE is rich in anthocyanins, exhibiting intense blue color and phenolic compounds present in this fruit shows antioxidant, anti-inflammatory, antitumor, and antimicrobial activity. [ 6 7 8 ] One fruit belonging to Ericaceae family, the Cranberry (CRAN), is a native fruit of North America used as a folk remedy by native inhabitants to clean kidneys, bladder and to treat urinary tract and gastrointestinal infections. [ 9 10 ] CRAM is exported to other regions of the world dried or processed into juice, like other berry fruits, is rich in phenolic acids, flavonoids, and terpenes.…”
Section: Introductionmentioning
confidence: 99%
“…The term nutraceutical derives from ‘nutrition’ and ‘pharmaceutical’ and many definitions can be found in the dictionaries. On a broader meaning, nutraceutical is a food which provides health benefits other than its nutritional value and that contains bioactive compounds which interact at different levels with the animal physiology [97,98,99,100,101,102,103,104,105,106,107,108,109,110,111,112,113,114]. Probiotic, prebiotic, secondary plant metabolites, amino acids, peptides, fatty acids, and essential oils are a non-exclusive list of nutraceutical compounds and, in this review, we will focus on secondary plant metabolites, probiotics, and prebiotics.…”
Section: Functional Compounds In Animal Nutritionmentioning
confidence: 99%
“…Grape polyphenols are considered as potent antioxidants and several studies in human have been conducted, as it can be seen from recently published reviews [125,126]. Even if grape polyphenols can be found in commercial supplements and complete diets for companion animals, in literature no scientific publication in this field are found, while few published studies are available for ruminants [99,100,105,109,110,114]. Interestingly, a common outcome of these studies was a significant increase of antioxidant activity at a blood level, measured as either biochemical markers or gene expressions.…”
Section: Functional Compounds In Animal Nutritionmentioning
confidence: 99%
“…These results were consistent with the previous reports that demonstrate there are active anti-inflammatory phytochemicals of different plant extracts. For example, previous studies have reported that analgesic and anti-inflammatory activities of various phytochemicals: suppression of the transcription of pro-inflammatory mediators by [6]-gingerol of ginger (Young et al 2005); anti-inflammatory activities in H 2 O 2stimulated macrophages by E. angustifolia L. extract (Pomari et al 2014); and inhibition of iNOS PeerJ reviewing PDF | (2017:02:16299:1:2:NEW 27 Apr 2017)…”
Section: Discussionmentioning
confidence: 99%